Interaction analysis of a concentric component evaporator absorber for an absorption heat transformer. (25th July 2018) - Canela-Sánchez, I.J.; Delgado-Gonzaga, J.; Huicochea, A.; Esche, E.; Repke, J.-U.; Saravanan, R.; Juarez-Romero, D.
Abstract: This work focuses on the analysis of a concentric component evaporator-absorber for an absorption heat transformer for water distillation by a H2O-LiBr refrigerant-absorbent pair. To understand the interrelationship of evaporation and absorption in this component and to identify the limiting mass and energy phenomena, a numerical model was built. This model describes the falling film heat transfer and the distillation inside of tubes per ring of coil. To make a precise specification of the conditions at which the transport properties are evaluated, the MOSAIC modeling framework was used. The model results were compared with experimental tests at steady state. Also, the effect of an increase in the composition of the absorption mixture was studied. The model was also useful to analyze the effect of the operating pressure in the dual component. The results showed that with an increase in the pressure from 17.68 to 21.33 kPa, the heat load in the evaporator decreases from 1.73 to 1.57 kW, and as result, the distilled water in the absorber decreases from 5.5 × 10 - 4 to 4.4 × 10 - 4  kg/s. This computational model identifies the effect of wetting efficiency in the evaporator as the limiting factor.